MENGENAL OTONOMI DAERAH SEBAGAI LANDASAN DEMOKRASI PEMERINTAH DAERAH DI INDONESIA - Ajidin, Asep (Ensiklopedia of Journal, 2021)
Democracy occupies a vital position in relation to the distribution of power in a country (generally based on the concept and principle of trias politica) with state power obtained from the people must also be used for the welfare and prosperity of the people. The principle of such a trias politica becomes very important to be taken into account when historical facts record that the government's (executive) power is so large that it is not able to form a just and civilized society, even the absolute power of the government often results in violations of human rights. Historically, the existence of regional government has been known since the reign of the ancestral kingdoms until the system of government imposed by the colonial government. The same applies to the social system and the structure of government, starting from the village, village, nagari, or in other terms to the top of the government leadership. Besides that, it is also very important to make a comparison of the system of government prevailing in other countries as a consideration for the formation of regional government. The provincial area apart from being a Region is also an Administrative Region which is the working area for the governor as a representative of the Central Government and the working area for the governor in carrying out general government affairs in the provincial area. A regency/municipal area apart from having the status as a Region is also an Administrative Region which becomes the working area for the regent/mayor in carrying out general government affairs in the regency/city area.